Study of Multiple 2:1 and Single 1:1 inlet/outlet ratio for serpentine PEMFC performance / Khairul Imran Sainan ... [et al.] - Sainan, Khairul Imran; Tijani, Alhassan Salami; Zakaria, Irnie Azlin; Wan Mohamed, Wan Ahmad Najmi (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Experimental analysis of channel inlet/outlet ratio assessment for a single cell PEM Fuel Cell (PEMFC) is presented in this paper. Two single cell fuel cells were compared with different channel inlet/outlet quantity of 1:1 inlet/outlet and multiple 2:1 inlet/outlet ratio. Fuel cell having single inlet has to overcome large pressure drop. Therefore, an additional inlet was introduced and compared. The two inlets of multiple 2:1 fuel cell were positioned far from each other to increase reactant distribution. The BPP were made from industrial standard carbon graphite. Nafion 112 PEM layer with an active area of 25 cm2 was used. Both fuel cells were subjected to similar experimental condition for comparison purposes. Both cathode and anode air condition supplied was dehumidified. Flow rates of 0.25 L/min, 0.5 L/min and 0.75 L/min were introduced at the cathode. Meanwhile, the anode hydrogen supplied was kept at a constant flow rate of 0.25 L/min. The results for each parametric condition was observed. The results show that polarization performance of 2:1 has improved over the 1:1 fuel cell. The 2:1 recorded average power improvement of 43.6%, 52.9%, and 47.2% over the 1:1 fuel cell for 0.25, 0.5 and 0.75 L/min cathode flow conditions. This shown that under similar operating conditions, additional inlet and the inlets positioning able to overcome pressure drop and promotes cell performance due to better reactant distribution.